A homozygous pathogenic missense variant broadens the phenotypic and mutational spectrum of CREB3L1-related osteogenesis imperfecta. (16th January 2019) - Guillemyn, Brecht; Kayserili, Hülya; Demuynck, Lynn; Sips, Patrick; De Paepe, Anne; Syx, Delfien; Coucke, Paul J; Malfait, Fransiska; Symoens, Sofie
Abstract: The cyclic adenosine monophosphate responsive element binding protein 3-like 1 ( CREB3L1 ) gene codes for the endoplasmic reticulum stress transducer old astrocyte specifically induced substance (OASIS), which has an important role in osteoblast differentiation during bone development. Deficiency of OASIS is linked to a severe form of autosomal recessive osteogenesis imperfecta (OI), but only few patients have been reported. We identified the first homozygous pathogenic missense variant [p.(Ala304Val)] in a patient with lethal OI, which is located within the highly conserved basic leucine zipper domain, four amino acids upstream of the DNA binding domain. In vitro structural modeling and luciferase assays demonstrate that this missense variant affects a critical residue in this functional domain, thereby decreasing the type I collagen transcriptional binding ability. In addition, overexpression of the mutant OASIS protein leads to decreased transcription of the SEC23A and SEC24D genes, which code for components of the coat protein complex type II (COPII), and aberrant OASIS signaling also results in decreased protein levels of SEC24D. Our findings therefore provide additional proof of the potential involvement of the COPII secretory complex in the context of bone-associated disease.